Fabrication of layered nanostructures by successive electron beam induced deposition with two precursors: Protective capping of metallic iron structures - Schirmer, Michael; Walz, Marie-Madeleine; Papp, Christian; Kronast, F.; Gray, A.X.; Balke, B.; Cramm, S.; Fadley, C.S.; Steinrück, Hans-Peter; Marbach, Hubertus (Nanotechnology, 2011)
We report on the stepwise generation of layered nanostructures via electron beam induced deposition (EBID) using organometallic precursor molecules in ultra-high vacuum (UHV). In a first step a metallic iron line structure was produced using iron pentacarbonyl; in a second step this nanostructure was then locally capped with a 2-3nm thin titanium oxide-containing film fabricated from titanium tetraisopropoxide. The chemical composition of the deposited layers was analyzed by spatially resolved Auger electron spectroscopy. With spatially resolved x-ray absorption spectroscopy at the Fe L edge, it was demonstrated that the thin capping layer prevents the iron structure from oxidation upon exposure to air. © 2011 IOP Publishing Ltd.